2010
DOI: 10.1021/la101172f
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Solution-Phase HNO2 Decomposition on the Electrocatalytic Nitrite Reduction at a Hemin−Pyrolitic Graphite Electrode

Abstract: The mechanism of nitrite electroreduction by hemin adsorbed at pyrolitic graphite is investigated. Two main issues are addressed: the effect of the medium pH and the selectivity of the reaction, which was determined by the combined use of the rotating ring disk electrode (RRDE) and online electrochemical mass spectroscopy (OLEMS). In acidic media, the behavior observed is indicative of the presence of NO, as the main reactant, generated from the solution-phase decomposition of HNO(2). Reduction of the NO-heme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
0
18
1
Order By: Relevance
“…12 An example of the former case would include the reduction of nitrate and nitrate on platinum electrodes, although other side reactions are known to play a role in these processes as well. [52][53][54] The protonated form of nitrite, nitrous acid, is known to be the more reactive species of the two. Nitrate reduction is also significantly faster in acidic media, 52 and the availability of protons should be considered as one of the determining factors for nitrate activation.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…12 An example of the former case would include the reduction of nitrate and nitrate on platinum electrodes, although other side reactions are known to play a role in these processes as well. [52][53][54] The protonated form of nitrite, nitrous acid, is known to be the more reactive species of the two. Nitrate reduction is also significantly faster in acidic media, 52 and the availability of protons should be considered as one of the determining factors for nitrate activation.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Usually, Au is a poor catalyst for NO 3 − reduction 40 in mildly acidic conditions, unless Cd +2 is present in the solution: in this case, underpotentially-deposited Cd selectively enhances the formation of NO 2 − 129, 130 . Nitrite is then targeted by hemin leading to NH 3 OH + , which is by far the major reduction product 131 . Despite failing to achieve 100% selectivity to N 2 , this 45 approach is very promising and should garner more attention.…”
Section: Perspectivesmentioning
confidence: 99%
“…Recently, it was reported that hemin could be adsorbed on graphene surface by -interactions to form complex nanosheets, which were exhibiting great properties and various applications. Meanwhile, it is worthy noted that many small molecules including nitric oxide [13], nitrite [15], and hydrogen peroxide [16] could be reduced or oxidized based on the active groups of hemin [17] or reversible redox potential of Fe 2+/3+ [18].…”
Section: Introductionmentioning
confidence: 99%